Mechanical Properties, Morphology and Biodegradability of Biopolymer Composites Prepared from Thermoplastic Starch and Polybutylene Succinate Reinforced with Rice Straw Fiber - Charerntanom, Wissanu; Buddhakala , Moragote; Buddhakala, Nopparat (Trends in Sciences, 2025)
Plastic utilization is increasing extensively with an increase serious impacts to human health and environment due to difficult degradation of petroleum-based plastics. This study was designed to develop biodegradable plastics from thermoplastic starch (TPS) and polybutylene succinate (PBS) reinforced with rice straw fiber (RSF) and investigate mechanical and physical properties, morphology and biodegradability of these plastic to verify whether they can be used as a petroleum-based plastic replacement. The biopolymer composites were prepared from TPS and BTS reinforced with various RSF content of 0, 10, 15, 20, 25, 30, and 35 %. The composites were prepared in an internal mixer at a temperature of 145 °C for 15 min and molded in Hot Compression Molding at 145 °C. The tensile test, impact test, hardness test, flexural test along with morphological examination and biodegradability determination were performed. The results revealed that tensile strength and tensile modulus increased while elongation at break decreased with increasing RSF content. Also, increasing RSF content increased hardness and flexural modulus but decreased impact strength. Scanning electron micrographs demonstrated the composites uniform and compact surface structure, homogenously and effectively distribution, interfacial adhesion of the RSF within the matrix and decreased spaces in the matrix replaced by the RSF. The morphological characteristics of the composites were correlated with physical and mechanical properties. The biodegradability of the composites was influenced by the RSF content and duration of soil burial treatment. The biopolymer composites developed from TPS and PBS reinforced with RSF can be used as a replacement of petroleum-based plastics and provide the sustainable, biodegradable, low cost, and environmental friendly bioplastics, especially reinforced with 30 % RSF. HIGHLIGHTS Rice straw, a natural material with high productivity from renewable resources and low cost provides an excellent fiber substance for the development of biodegradable plastics to replace petroleum-based plastics. Rice straw fiber as a reinforcement can improve the mechanical properties, morphology and biodegradability of the biopolymer composites. Biopolymer composites prepared from TPS and PBS reinforced with RSF could provide the sustainable, biodegradable, low cost as well as the environmental friendly bioplastics. Utilization of rice straw fibers as a reinforcing agent in thermoplastic composites could decrease negative impact from rice straw open - burning and value-added of rice straw. GRAPHICAL ABSTRACT